(untitled) (European Journal of Emerging Technology and Discoveries, 2024)
This article provides an overview of the uArm Swift, a robotic arm designed for various applications in industrial and home settings. The uArm Swift offers features such as programmability, repeatability, and flexibility, making it suitable for tasks such as prototyping, simulation, and recommended control algorithms. The article highlights the importance of repeatability in industrial robots and explains how the uArm Swift Pro model ensures high precision with a repeatability of 0.2mm. The article also discusses the modular design of the manipulator, including options such as a laser engraving module and a camera module, as well as the uArm Studio software for easy control and programming. The uArm Swift’s user-friendly interface allows users to control the robot through block programming or by manually demonstrating desired movements. The article concludes by mentioning the advancements in the uArm Swift Pro model, which includes increased degrees of freedom, improved power button, offline learning mode, and interchangeable end-effectors.